DNA copy number aberrations and expression of ABC transporter genes in breast tumour: Correlation with the effect of neoadjuvant chemotherapy and prognosis of the disease - Tsyganov, Matvey M.; Ibragimova, Marina K.; Gaptulbarova, Kseniya A.; Tsydenova, Irina A.; Dolgasheva, Daria S.; Garbukov, Evgeny Yu; Frolova, Anastasia A.; Slonimskaya, Elena M.; Litvyakov, Nicolay V. (Pharmaceutics)
One of the important reasons for the ineffectiveness of chemotherapy in breast cancer (BC) is considered to be the formation of a multidrug resistance phenotype in tumour cells, which is caused by the expression of energy-dependent ABC transporters. The aim of this work was to assess chromosomal aberrations and the level of transcripts of all 49 known ABC transporter genes in breast tumours. Materials and Methods. The study included 129 patients with breast cancer. A microarray study of all tumour samples was carried out on microchips. Results. This study established that the presence of a deletion in genes ABCB1, ABCB4, ABCB8, ABCC7, ABCC11, ABCC12, ABCF2, and ABCG4 is associated with an objective response to treatment (p <= 0.05). A decrease in the expression of genes was associated with a good response to chemotherapy, whereas an increase in expression caused the progression and stabilization of the tumour. Analysis of metastatic-free survival rates showed that the presence of ABCB1/4 and ABCC1/6 deletions was associated with 100% survival (log-rank test p = 0.01 and p = 0.03). Conclusions. The study showed that the aberrant state of ABC transporter genes, as well as a decrease in the expression of these genes, is a predictor of the effectiveness of therapeutic treatment and a potential prognostic marker of metastatic survival.